Impedance analysis of adherent cells after in situ electroporation-mediated delivery of bioactive proteins, DNA and nanoparticles in µL-volumes - Judith A. Stolwijk (Nature Portfolio, 2020)
Abstract Specific intracellular manipulation of animal cells is a persistent goal in experimental cell biology. Such manipulations allow precise and targeted interference with signaling cascades, metabolic pathways, or bi-molecular interactions for subsequent tracking of functional consequences. However, most biomolecules capable of molecular recognition are membrane impermeable. The ability to introduce these molecules into the cytoplasm and then to apply appropriate readouts to monitor the corresponding cell response could prove to be an important research tool. This study describes such an experimental approach combining in situ electroporation (ISE) as a means to efficiently deliver biomolecules to the cytoplasm with an impedance-based, time-resolved analysis of cell status using electric cell-substrate impedance sensing (ECIS). In this approach, gold-film electrodes, deposited on the bottom of regular culture dishes, are used for both electroporation and monitoring. The design of the electrode layout and measurement chamber allows working with sample volumes as small as 10 µL. A miniaturized setup for combined electroporation and impedance sensing (µISE-ECIS) was applied to load different adherent cells with bioactive macromolecules including enzymes, antibodies, nucleic acids and quantum dot nanoparticles. The cell response after loading the cytoplasm with RNase A or cytochrome c (in the presence or absence of caspase inhibitors) was tracked by non-invasive impedance readings in real-time.